Principal's Strategy In Improving Student Achievement - Affan Affan; Usman Usman; Muhammad Rusmin; Mardhiah Mardhiah; Baharuddin Baharuddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to describe the principal's strategy in improving student achievement at Al-Azhar Palu Junior High School, the implementation of the strategy, and the impact it causes. The main problem raised in this study is how the principal’s strategy is to improve the achievement of students at Al-Azhar Palu Junior High School. This study uses a descriptive qualitative approach with the perspective of Islamic Education Management. Data was collected through observation, in-depth interviews, and documentation, and analyzed through the stages of checking, grouping, examination, and drawing conclusions. The validity of the data is tested through credibility, transferability, dependability, and confirmability techniques. The results of the study show that the principal’s strategy at Al-Azhar Palu Junior High School has succeeded in improving the achievement of students as a whole, both in the academic, non-academic, and character formation fields. The strategies implemented include an interest- and talent-based approach, student-centered learning, and collaborative management between teachers, parents, and students. Strengthening character values such as discipline, responsibility, and the spirit of learning is also an integral part of the strategy. The implementation of the strategy is supported by a clear school vision, excellent programs, continuous improvement of teacher competence, and periodic evaluations. The impact can be seen from the increase in motivation, confidence, learning quality, and student achievement in various fields. The implications of this study suggest that the principal's adaptive and collaborative strategic approach can be a model for the development of student achievement in other schools, emphasizing the importance of visionary leadership, teacher professional development, and synergy between schools and parents.